Polystyrene functional high polymer material of polystyrene lateral chain supported schiff base and preparation thereof - XU GAOYANG; MA JUANJUAN; ZHANG TIANLIN; ZHANG DONGEN; TONG ZHIWEI (2009)
The invention relates to a functional polymer material of a polystyrene side chain-supported Schiff base quaternary ammonium salt or Schiff base internal salt, which can form complex supermolecular system of different colors and different fluorescence emission or fluorescent quenching characteristics with various metallic ions. The functional polymer material can be used in qualitative analysis and quantitative analysis of heavy metal ions in industrial waste water, rivers, lakes or oceans, and can also be used for separating, collecting and recycling the heavy metal ions.